THE INFLUENCE OF PLAY THERAPY: SKILL PLAY ON ABILITY SELF CARE WITH MENTALLY RETARDED CHILDREN IN SLB/C KUMALA II SURABAYA A - Abdul Fatah Maushun (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: to analyze the Influence of Play Therapy: Skill Play on Ability Self Care With Mentally Retarded Children in SLB/C Kumala II Surabaya A . Methods: This research used One group pretest-postest desain. The population of mentally retarded children in SLB/C Kumala II Surabaya. Total sample was 32 respondents, enrolled using purposive sample method. Data were collected using questionnaire and observation, data were analyzed by Wilcoxon Test with significant level p<0.05. Results: The result showed that play therapy: skill play had strong influence to ability self care for mentally retarded children, with the result adequate self care is 4 persons (12,5%), and less self care is 28 persons (87,5%). After play therapy that adequate self care is 18 persons (56,2%), and less self care is 14 persons (46,8%). It’s mean that play therapy: skill play have influence for ability self care of mentally retarded children. That result can evidence with value P: 0.000< 0.05 under value. Conclusion: It can be concluded that there is significant influence of play therapy: skill play for ability self care of mentally retarded children. Further play therapy applied for child with mental retardation to increase ability self care to increase developmental independent patients with the aim to support the establishment of a positive self-concept.